2016
DOI: 10.1038/srep37402
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating effects of ex situ application of rice straw on CH4 and N2O emissions from paddy-upland coexisting system

Abstract: The in situ application of rice straw enhances CH4 emissions by a large margin. The ex situ application of rice straw in uplands, however, may mitigate total global warming potential (GWP) of CH4 and N2O emissions from paddy-upland coexisting systems. To evaluate the efficiency of this practice, two field trials were conducted in rice-rice-fallow and maize-rape cropping systems, respectively. Year-round measurements of CH4 and N2O emissions were conducted to evaluate the system-scaled GWP. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 43 publications
2
24
1
Order By: Relevance
“…In double-rice-cropping systems, straw retention also significantly increased CH 4 and reduced N 2 O emission [34]. However, Wang et al [35] and Wu et al [36] showed that rice straw incorporation increased the field's N 2 O emissions. GHG emissions in paddy fields were sensitive to the straw retention mode, for instance, emissions of CH 4 and N 2 O in paddy fields with straw mulching were lower than those with straw incorporation into the soil [37].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In double-rice-cropping systems, straw retention also significantly increased CH 4 and reduced N 2 O emission [34]. However, Wang et al [35] and Wu et al [36] showed that rice straw incorporation increased the field's N 2 O emissions. GHG emissions in paddy fields were sensitive to the straw retention mode, for instance, emissions of CH 4 and N 2 O in paddy fields with straw mulching were lower than those with straw incorporation into the soil [37].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, straw retention affects CH 4 and N 2 O emissions by changing the soil's physical and chemical properties. Straw incorporation can decrease the soil's oxygen content during the rice season and provide organic substrates for microbial methanogens, thereby increasing the paddy field's CH 4 emissions [1,11,34,35,38]. The effect of straw incorporation on N 2 O emission is still controversial [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This generates approximately 1140 million tons of rice straw considering the fact that approximately 1.5 tons of rice straw is generated per ton of rice. About 50% of rice straw is burnt in the field while the remaining is utilized as fodder or used in the wood‐composite industry, or left, as such, to decompose in landfills . Inefficient burning of rice straw releases large amounts of harmful gases including carbon monoxide, polycyclic aromatic hydrocarbons, volatile organic compounds, and nitrous oxides, along with suspended particulate matter .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Ineffi cient burning of rice straw releases large amounts of harmful gases including carbon monoxide, polycyclic aromatic hydrocarbons, volatile organic compounds, and nitrous oxides, along with suspended particulate matter. 6 Th is leads to alarming levels of environmental pollution and represents a tremendous waste of lignocellulosic biomass resource. Hence, there is an urgent need to develop high-volume, value-added conversion technologies to harness the energy potential of surplus rice straw.…”
Section: Introductionmentioning
confidence: 99%